The Van Gogh Cafe - Rylant, Cynthia (San Diego : Harcourt Brace, 1995)
The Van Gogh Cafe, located in Flowers, Kansas, has magic in its walls, causing strange and mysterious events to occur there.
Wilson's Children.
Wilson's Junior High School.
Elem. School Library Collection.
4.5
3-6
810L
Keywords: Restaurants -- Fiction; Magic -- Fiction